2001
DOI: 10.1046/j.1460-9592.2001.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia for circumcision in a paediatric population: comparison of caudal bupivacaine alone with bupivacaine plus two doses of clonidine

Abstract: For paediatric circumcision, under general anaesthesia, the addition of clonidine 2 microg x kg(-1) to low volume (0.5 ml x kg(-1)) caudal anaesthetics has a limited clinical benefit for children undergoing circumcision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 27 publications
(75 reference statements)
1
63
0
2
Order By: Relevance
“…This result is not consistent with the results of the studies that used clonidine (2 µg/kg) with a low concentration (0.125%) of bupivacaine (1 mL/kg), in which analgesic efficacy was not significantly improved. [22][23][24] The authors of those studies speculated that clonidine 2 µg/kg may not be effective with a lowconcentration of bupivacaine, although the exact mechanism is unclear. However, DEX is a more selective α2-adrenoceptor agonist and is eight times potent than clonidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is not consistent with the results of the studies that used clonidine (2 µg/kg) with a low concentration (0.125%) of bupivacaine (1 mL/kg), in which analgesic efficacy was not significantly improved. [22][23][24] The authors of those studies speculated that clonidine 2 µg/kg may not be effective with a lowconcentration of bupivacaine, although the exact mechanism is unclear. However, DEX is a more selective α2-adrenoceptor agonist and is eight times potent than clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, caudal DEX with a low-concentration of local anesthetics induces less adverse effects (motor weakness, delayed micturition of urinary retention) that may affect early discharge from hospital, compared with a higher concentration of local anesthetics. 3,4,10,12,13,23) DEX has anxiolytic, sedative, and hypnotic properties caused by stimulation of the α2-adrenoceptor in the locus coeruleus in brain where it decreases a neuronal activation 9,24) and can reduce the requirement of concomitantly administered hypnotics, analgesics, or anesthetics. 25) Intravenous DEX significantly decreases the sevoflurane requirement 5,26) for anesthesia and EA during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…167,168 There is good evidence for a high incidence of mild postoperative motor block and delay in walking after the CB procedure (21% to 44%) in older children. 167,169,170 Caudal analgesia may be less available in facilities that do not treat many pediatric patients.…”
Section: Caudal Blockmentioning
confidence: 99%
“…Our findings corroborate with previous studies. 7,8,9,10 which have reported clonidine 1-2mcg/kg added to bupivacaine for caudal block increase the duration of analgesia in small children undergoing ambulatory hernia repair and sub umbilical surgeries compared to bupivacaine alone.…”
Section: Discussionmentioning
confidence: 99%
“…10 which can be explained by the fact that the quality, level and duration of caudal blockade depends on the dose, volume and concentration of the drugs injected authors compared the duration of postoperative analgesia in children undergoing hypospadiasis repair with different volumes and concentration of fixed doses of ropivacaine local anaesthetic and concluded that high volume low concentration regime produces prolonged analgesia as compared to low volume high concentration. Our data with clonidine for caudal block corroborate with those results of previous studies.…”
Section: Discussionmentioning
confidence: 99%